Error-driven decision and error condition word for continuous hot press flocking control system. (2016) - Wu, Qu; Lv, Bo; Liu, Yaqiu; Zhu, Liangkuan
To aim at efficient and reliable coding for error data in an error-driven control system, an error condition word (ECW) coded by hamming specification is proposed. For continuous hot press flocking motion terminals control system which is based on hierarchical structure of synergetic governance, ECW is recognised by hamming tree to determine error information and to carry out sub-decision matrix. Numerical analysis and simulation indicate that ECW can drive the system to carry out appropriate decisions so as to command flocking motion terminals to execute output presenting hierarchical synergy. In contrast with fuzzy control, the data bits of error condition used ECW and hamming tree present logarithmic growth as the length of error data bits increases, not linear. Within certain range of limited bits, the number of error level is permitted to increase. Usage of ECW makes optimisation for controller more convenient.